New Insights Into the Phylogeny and Biogeography of Goji Berries ( Lycium , Solanaceae) Inferred From Plastid Data - Gulbar Yisilam; Kenneth M. Cameron; Zhi‐Yong Zhang; En‐Ting Zheng; Chuan‐Ning Li; Zhen‐Zhou Chu; Ying Su; Jia‐Lei Li; Yu‐Wei Wang; Jin Li; Pan Li; Xin‐Min Tian (Journal of Biogeography, 2025)
Aim Lycium L. (Solanaceae), which is known for producing goji berries, is an important plant with both medicinal and edible uses. This genus is globally distributed in temperate and subtropical regions. However, a comprehensive phylogeny and evolutionary history of this plant group is lacking so far. This study was executed to produce novel insights into the phylogenetic relationships and evolutionary history of this small but economically important genus. Location North America, South America, Hawaii, Africa and Eurasia. Taxon Lycium L. (Solanaceae). Methods We established a phylogenetic framework for Lycium based on complete plastome sequences and data from 80 protein‐coding genes across 43 Lycium species using maximum likelihood and Bayesian inference methods. Furthermore, 14 species from the Solanaceae family were used as outgroups. Additionally, two Solanoideae fossils and one secondary calibration point were used to estimate divergence times and reveal the biographical history of these plants through ancestral area reconstruction. Results Our analysis revealed that six North American Lycium species were strongly supported as monophyletic with high support and were sister clades to the remainder of the genus. The remaining species from North America, South America and the Hawaiian Islands shared a common ancestor, whereas all species from Africa, Saharo‐Arabia and Eurasia formed a distinct clade. Our results indicated that Lycium originated in North America during the Late Oligocene and then dispersed to Hawaii and South America, from there to Africa, and then further to Saharo‐Arabia, with a more recent dispersal to Eurasia. Main Conclusions Our plastid genome data confirmed that Lycium originated in North America and identified long‐distance dispersal as the key to its global distribution. Genomic insights facilitate species identification and contribute to conservation efforts.